Emergency contraception: a survey of 1773 women. (1st November 2016) - Bastianelli, Carlo; Rosato, Elena; Farris, Manuela; Benagiano, Giuseppe
Abstract: Objectives: The aim of the study was to retrieve data on the characteristics and profile of women attending an emergency service (ES) to receive a prescription (mandatory until May 2015) for emergency contraception (EC). Methods: In a retrospective study the following data were collected for all women requesting EC between January 2014 and June 2015: demographic characteristics, time between unprotected sexual intercourse (USI) and arrival at the ES, time between the last menstrual period and the USI, and type of EC prescribed. In a prospective study starting January 2015, a questionnaire was administered requesting the following information: reasons for requiring EC, previous EC use, source of knowledge about EC, prior contraception and age at first intercourse. Results: During the whole study period, 1773 women requested EC: their mean age was 26.0 years; 78.5% were Italian; 91.5% were unmarried; 55.2% were still studying and 51.9% had high school education; 61.2% reached the ES within 12 h of the USI; and 42.4% had a USI during days 9–16 of their menstrual cycle. Levonorgestrel was prescribed in 81.4% of women and ulipristal acetate in 17.7%. In the prospective part of the study (382 women), the majority (57.9%) requested EC for condom rupture; 49.5% reported previous use of EC; and 41.6% received information on the subject through friends. The vast majority (83.8%) reported prior use of contraception; in 25.4% the reason for not using it was the absence of a relationship. Conclusion: An exact profile of women requesting EC can help women in their choice of permanent contraception, and help clinicians in counselling women on appropriate contraception.